STATUS KESEHATAN PADANG LAMUN DI PERAIRAN DESA TANAKI KECAMATAN SIAU BARAT SELATAN KABUPATEN SITARO - David B. Tamarariha; Calvyn F. A. Sondak; Veibe Warouw; Grevo S. Gerung; Billy Th Wagey; Anneke V. Lohoo (Sam Ratulangi University, 2022)
Siau Island is a part of Sitaro Archipelago located in northern part of Sulawesi Island. This island is rich of marine biodiversity include mangrove, coral reef and seagrass bed. The purposes of this study were to identify seagrass species, cover area and its health status. This research was conducted from September to October 2021, in Tanaki Village waters, Siau Island. The research method that used in this study is the quadrant transect method which includes the calculation of seagrass cover within station and seagrass species percent cover that used to determining the health status and condition of seagrass beds. Seven seagrass species were found in Tanaki water namely Cymodocea rotundata, Thalassia hemprichii, Enhalus acoroides, Syringodium isoetifolium, Halodule pinifolia, Halophila ovalis and Thalassodendron ciliatum. The health status of the seagrass beds in the study area was categorized